A Murine Toolbox for Imaging the Neurovascular Unit. (April 2015) - Hartmann, David A.; Underly, Robert G.; Watson, Ashley N.; Shih, Andy Y.
Abstract The neurovascular unit (NVU) coordinates many essential functions in the brain including blood flow control, nutrient delivery, and maintenance of BBB integrity. These functions are the result of a cellular and molecular interplay that we are just beginning to understand. Cells of the NVU can now be investigated in the intact brain through the combined use of high‐resolution in vivo imaging and non‐invasive molecular tools to observe and manipulate cell function. Mouse lines that target transgene expression to cells of the NVU will be of great value in future work. However, a detailed evaluation of target cell specificity and expression pattern within the brain is required for many existing lines. The purpose of this review was to catalog mouse lines available to cerebrovascular biologists and to discuss their utility and limitations in future imaging studies.